Ability of Different Heat-treated Egg Yolk Lipids to Alleviate Cognitive Decline in Mice - Yao WU; Mingkun LIU; Bing FANG; Ming ZHANG (Shipin gongye ke-ji)
To investigate the differences in the ability of egg yolk lipids to alleviate the decline in learning and cognitive abilities in mice under different temperature treatments. This study utilized a mouse model of cognitive impairment to compare the varying impacts on learning and cognitive functions resulting from 95 ℃ (30 min in water bath) and 121 ℃ (30 min in sterilization pot) heat treatments of egg yolk lipid components. The research results showed that compared with 121 ℃ heat treatment of egg yolk lipids, 95 ℃ heat treatment of egg yolk lipids effectively reduced the phosphorylation of Tau protein and the expression of Aβ1-40 and GSK-3β, downregulated the expression of pro-inflammatory factors, and had a better effect on improving the learning and memory abilities of mice. The levels of polyunsaturated fatty acids and DHA in 95 ℃ heat treatment of egg yolk lipids were significantly increased compared to those treated at 121 ℃ (P<0.05). The above results demonstrated that excessive heating impaired the ability of egg yolk lipids to alleviate cognitive decline, which might be related to the thermal degradation of polyunsaturated fatty acids such as DHA in egg products. This study provides a basis for the optimization of thermal processing of nutritious and healthy egg products.